Which Are The Competitive Benefits From Implementing The Project Management Maturity Framework? Based On The Case Company. - Arancibia, Daniela (2010)
ABSTRACT Project Management became popular in the early 60s, but it was until the 90s that this was considered as a core capability in the companies. During the late 80s there was the creation of the first maturity model, the Capability Maturity Model (CMM) developed for the software industry. So it was only during the late 90s when maturity models were started to be mentioned on different industries, and during the next years many models were created: Standardized Process Improvement for Construction Enterprises, SPICE, Project Management Maturity Model, PMMM, Portfolio, Programme and Project Management Maturity Model, P3M3, Organizational Project Management Maturity Model, OPM3. In this dissertation all these models are described, and there is a case study where small a construction company, ICEAL, is assessed with two of these models: SPICE, and P3M3.